代間學習策略融入社會老年學之學習歷程與成效研究 Learning Process and Effects of Incorporating Intergenerational Learning in a Social - 陳毓璟 Stephanie Yu-Ching Chen (National Taiwan Normal University, 2014)
本研究旨在探討代間學習策略融入「社會老年學」課程之學習歷程與成效，採質量並重的混合研究。透過不等組前後測準實驗設計和對照質性資料之交叉檢視，來探究課程中代間互動與學習歷程，以及代間學習的成效。研究對象為48位大學生，22位實驗組與15位隨班附讀的高齡者，進行18週的共同學習。結果發現，不同世代的學習者從原本敬老尊賢的尊卑態度逐步發展為學習夥伴的平等關係，透過不斷地互動與對話，學生逐步瞭解高齡者，並且提升溝通能力與同理心。雖然代間學習策略無法顯著提升學生的老化知識，但顯著改善學生對老人的態度與提升服務老人的意願。本研究依據教學過程歸納出七點代間學習教學設計參考原則，並針對未來課程設計與研究提出建議。 This study investigated the learning process and effects of incorporating intergenerational learning in a social gerontology course. The nonequivalent quasiexperimental research design, which involved combining qualitative and quantity methods, was adopted and co-inspected using qualitative data to explore the learning process and effects of intergenerational interaction. A total of 48 participants were included in this study. We invited 15 older adults to study together freely with 22 students in the experimental group for 18 weeks. The results showed that, through continual interaction and dialogue, the intergenerational relationship gradually developed from originally hierarchical, respecting the older adults, to the equal attitudes of the learning partners. The students understood the older adults, improved the communication skills, and developed empathy gradually. Although intergenerational learning did not substantially improve the knowledge of the students on aging, the attitudes of the students toward the older adults and willingness to serve elderly people markedly improved. Finally, seven principles of intergenerational learning instructional design, based on the instructional process, and recommendations for future courses and research design were suggested.